Using Macrocystis pyrifera (L.) C. Agardh from southern Chile as a source of applied biological compounds - Mansilla,Andrés (2011)
The exploitation of seaweeds in Chile has been carried out for more than 60 years. More recently, seaweeds have been used for the production of alginate, agar and carrageenan, agricultural fertilizers and industrial aquaculture (feed for abalone and sea urchins), increasing the added value of this natural resource. In the Magellan Region (56ºS), the giant kelp Macrocystis pyrifera (L.) C. Agardh presents the most extensive kelp forest, reaching a biomass of approximately 12 kg.m-2. Recent studies have shown potential benefits from adding M. pyrifera- derived flour to salmonid feed. Research is currently underway to evaluate the useof brown algae-derived products for marine aquaculture feed of Oncorhynchus mykiss in tanks. There was no apparent adverse effect on the evaluated parameters that can be attributed to the incorporation of M. pyrifera meal in the diets fed to salmonids. Even when the control diet had numerically the best performance in zootechnical terms, the analysis of variance of all parameters evaluated showed no significant differences with regard to diets containing M. pyrifera meal. These results demonstrated that seaweed meal has important benefits for animal health and nutrition that could be applied or tested in other marine organisms of commercial importance.